Design and optimization of a breast-dedicated SPECT scanner with multi-lofthole collimation. (4th January 2022) - Saed, M.; Sadremomtaz, A.; Mahani, H.
Abstract: Background : the need for simultaneous high-sensitivity and high-resolution breast SPECT imaging mandates to design and optimize dedicated scanners. Therefore, this work aims to design and optimize a novel breast-dedicated SPECT system with multi-lofthole collimator. Materials and Methods : in this research, a novel breast-dedicated scanner is designed and then optimized. The scanner is equipped with a single full-ring multi-lofthole collimation long with modular NaI(Tl) detectors. The step-and-shoot data acquisition was considered with two steps. Then, an analytic optimization was conducted to balance the existing sensitivity-resolution tradeoff. To do so, several scanner geometries were investigated. The optimal configuration maximized the system sensitivity at a given system resolution. Furthermore, the scanner was also modeled within the GATE simulator. Then, detector energy resolution, septal penetration and scattering, and system sensitivity were calculated. Analytic findings were also compared with the simulated ones. Results : the results showed that high sensitivity of about 2 cps/kBq can be obtained for a diameter of lofthole 3.05 mm with a 75° opening angle. Results of GATE simulations showed clinically acceptable performance of the system offering 9% energy resolution for a point source. The septal penetration and scattering were approximately 0.5% and 0.2%, respectively, for cylindrical water phantom and tungsten as collimator material. Conclusion : the designed SPECT scanner provides promising results in terms of sensitivity and spatial resolution and therefore outperforms the traditional multi-pinhole collimation by a much higher sensitivity at a given system resolution.